PENGENTASAN KEMISKINAN DAN PENGEMBANGAN MASYARAKAT MELALUI MODEL KEUANGAN ISLAM BMT AL-ISHLAH CIREBON - Muhammad Awaluddin Ardiansyah (BISMA (Bisnis dan Manajemen), 2018)
Although in fact the conventional financial system has manifestly failed in the fair distribution of wealth, but Islamic financial system in Indonesia is not a strong alternative financial system. Market share of Islamic financial institutions are still low below 5% with growth of 34% in 2015. The data indicates the existence of problems in the implementation of the principles of Islamic finance though in terms of potential prospects. Islamic economic principles which have a charge values of justice, divinity, freedom and responsibility, the right should be a system of democratic economy in the economic empowerment of the poor. Some of the reasons based on the analysis of the field to be the cause of them; The first people are still accustomed to a conventional system that has been around longer, the second Islamic financial institutions are not ready completely adopt the Islamic financial system in particular lost Pofit product sharing (PLS), the third implementation of Islamic financial institutions require relatively high operating costs. On the above problems, the authors analyzed qualitatively descriptive of a theme study "Al-Islah BMT Cirebon as Islamic Financing Model for Poverty Reduction and Development". An analysis of the terms of the Muamalat Islamic law and court analyzes considering the author as a community development agency practitioners who use Islamic financial institutions Baitul Maat wa Tamwil (BMT) in technical operations. This simple paper notes that Islamic financial institutions in Indonesia has not fully practice the principles of Islamic finance because of certain interests. That has existed in Indonesia an Islamic financial institution which according to the principles of Islam in practice the empowerment of people out of poverty.